2000
DOI: 10.1046/j.1365-2141.2000.02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating normal B‐cell precursors during and after treatment of acute lymphoblastic leukaemia: implications for monitoring of minimal residual disease

Abstract: Summary. We studied 57 childhood acute lymphoblastic leukaemia (ALL) patients who remained in continuous complete remission after treatment according to the Dutch Childhood Leukaemia Study Group ALL-8 protocols. The patients were monitored at 18 time points during and after treatment [640 bone marrow (BM) and 600 blood samples] by use of cytomorphology and immunophenotyping for the expression of TdT, CD34, CD10 and CD19. Additionally, 60 BM follow-up samples from six patients were subjected to clonality assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
80
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 38 publications
11
80
0
2
Order By: Relevance
“…In normal BM of children, up to 15% of cells are precursor-B cells, whereas during BM regeneration (such as after stem cell transplantation or after chemotherapy courses) precursor-B cells may even comprise up to 50% of cells. 9,[12][13][14][15] Also in normal PB, precursor-B cells are found, although at low frequencies (up to 0.4%). 9,15 Consequently, 15 years ago no reliable comparison could be made between MRD levels in BM and PB samples of precursor-B-ALL patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal BM of children, up to 15% of cells are precursor-B cells, whereas during BM regeneration (such as after stem cell transplantation or after chemotherapy courses) precursor-B cells may even comprise up to 50% of cells. 9,[12][13][14][15] Also in normal PB, precursor-B cells are found, although at low frequencies (up to 0.4%). 9,15 Consequently, 15 years ago no reliable comparison could be made between MRD levels in BM and PB samples of precursor-B-ALL patients.…”
Section: Introductionmentioning
confidence: 99%
“…9,[12][13][14][15] Also in normal PB, precursor-B cells are found, although at low frequencies (up to 0.4%). 9,15 Consequently, 15 years ago no reliable comparison could be made between MRD levels in BM and PB samples of precursor-B-ALL patients. However, recent immunophenotyping data of Campana and CoustanSmith suggest that MRD levels are higher in BM than in PB in at least some precursor-B-ALL patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Expansion of hematogones may be persistent, for 2 years after completion of chemotherapy for ALL and for more than 1 year following BM transplantation. 4,5 No clear description of their increase after CB transplantation has been reported until now. Most recently, Shono et al 6 reported a case of non-clonal expansion of blastic-appearing CD19 þ CD20 þ lymphocytes in BM and PB of an adult recipient after unrelated CB transplant.…”
mentioning
confidence: 99%
“…Among the European groups, the sensitivity of flow cytometry using aberrant or 'leukemia-associated' immunophenotypes is controversially discussed, in particular concerning the separation of malignant from normal B-cell precursor (BCP) cells in regenerating bone marrow (BM). 5,6 However, in the BFM study, two fixed marker combinations for MRD detection in BCP-ALL are used, whereas Coustan-Smith and co-workers employ individual marker combinations depending on the specific immunophenotype of the patients including innovative leukemia-specific markers. 3 In the multicentre setting, the cost-effectiveness is an important argument in favour of flow cytometry; furthermore, this technique is less time consuming.…”
Section: To the Editormentioning
confidence: 99%
“…To prevent the possibility of phenotypic shift, we always recommend the use of multiple marker combinations whenever possible. [3][4][5][6] Likewise, more than one allele-specific oligonucleotide probe should be used with PCR to offset the risk of false-negative results due to oligoclonality and clonal evolution. 7 Regarding the sensitivity of flow cytometry, one should make a distinction between flow cytometric techniques that rely on combinations that are not expressed by normal hematopoietic cells (including hematogones) and those that use marker combinations that are not completely leukemia specific.…”
Section: To the Editormentioning
confidence: 99%